Supervisors’ social dominance orientation, nation-based exchange relationships, and team-level outcomes - Sajadi, Pegah; Vandenberghe, Christian (Frontiers in Psychology, 2022)
The prevalence of teams in contemporary organizations and the trend towards diversity in a workforce composed of members from multiple countries have drawn the attention of researchers on the consequences of diversity in workplaces. While there are potential benefits to diversity, relationship conflicts among team members may also result and affect team functioning. The present study explores the role of supervisors in influencing the relative quality of exchange relationships with team members from diverse nations and how this impacts relationship conflicts and team commitment. Specifically, we hypothesized that supervisor social dominance orientation, a tendency to support the arbitrary dominance of specific social groups over others, fosters within-team differentiation of leader-member exchange (LMX) relationships based on team members’ national origin. We further hypothesized that such LMX differentiation (LMXD) would increase within-team relationship conflict and in turn lead to reduced collective team commitment. A two-wave study among a sample of 931 individuals from 108 workgroups found support for these predictions. We discuss the implications of these findings for research on supervisor social dominance orientation, within-team nation based diversity, and team functioning.